Polishing powder, polishing solution and preparation method and application thereof

By combining the combination of large-particle and small-particle cerium oxide in the polishing powder, the defect problems such as scratches on the quartz glass substrate are solved, and high-efficiency polishing and excellent surface quality are achieved to meet the integrated circuit High requirements for manufacturing.

CN119242180APending Publication Date: 2025-01-03CHANGSHA SHAOGUANG CHROME BLANK
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411294320.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing cerium oxide polishing liquid is prone to scratches and other defects on the surface of quartz glass substrates, which affects the surface quality and makes it difficult to take into account both the polishing rate and the surface quality.

Method used

The polishing powder of cerium oxide A with a particle diameter D50 of 0.8 to 1.5 μm and cerium oxide B with a particle diameter D50 of 0.1 to 0.6 μm is used, and the mechanical scratching effect of large-particle cerium oxide A and small-particle cerium oxide B are used. High bulk density and adsorption capacity, combined with the use, adjust the particle size and ratio of polishing powder, and improve the polishing rate and surface quality.

Benefits of technology

High polishing efficiency and excellent surface quality are achieved, and large-particle cerium oxide A is prevented from excessive removal of the surface of the substrate from being depressed, ensuring the planarization of the substrate and the stability of the polishing liquid, and meeting the high requirements of integrated circuit manufacturing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005045484740000011
    Figure HDA0005045484740000011
  • Figure HDA0005045484740000012
    Figure HDA0005045484740000012
  • Figure HDA0005045484740000021
    Figure HDA0005045484740000021
Patent Text Reader

Abstract

The invention discloses a polishing powder, a polishing solution and a preparation method and application thereof. The polishing powder comprises cerium oxide A with the particle size D50 of 0.8-1.5 microns and cerium oxide B with the particle size D50 of 0.1-0.6 microns, the mass percent of the cerium oxide B is 10%-40%, and the polishing rate and the polishing surface quality of the polishing powder are jointly improved through mutual cooperation of the cerium oxide A with the large particle size and the cerium oxide B with the small particle size. The invention also provides a polishing solution and a preparation method thereof, and application of the polishing powder and the polishing solution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polishing materials, and in particular to polishing powder, polishing liquid, and a preparation method and application thereof. Background Art

[0002] In integrated circuit manufacturing, microfabrication using photolithography as the main method is a key technology for obtaining large-scale integrated circuits. As the requirements for miniaturization of photolithography patterns continue to increase, more stringent requirements are placed on the defect density and defect size, surface roughness, flatness and other qualities of the quartz mask substrate used in it.

[0003] Currently, the polishing liquid used for quartz polishing is mainly cerium oxide polishing liquid, which can achieve a higher polishing rate. However, the existing cerium oxide polishing liquid is prone to produce defects such as scratches on the surface of the quartz glass substrate, affecting the surface quality of the glass substrate.

[0004] Therefore, it is necessary to develop a polishing liquid that can balance polishing rate and good surface quality. Summary of the invention

[0005] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention provides a polishing powder which has high polishing efficiency and can ensure good polishing surface quality.

[0006] The invention also provides a polishing liquid.

[0007] The invention also provides a method for preparing the polishing liquid.

[0008] The invention also provides application of the polishing powder or polishing liquid.

[0009] Specifically, the first embodiment of the present invention relates to a polishing powder, comprising: cerium oxide A with a particle size D50 of 0.8 to 1.5 μm and cerium oxide B with a particle size D50 of 0.1 to 0.6 μm, wherein the mass percentage of cerium oxide B is 10% to 40%.

[0010] The polishing powder according to the first aspect of the present invention has at least the following beneficial effects:

[0011] Cerium oxide A is a large-particle polishing powder, which mainly plays a macroscopic mechanical scratching role during the polishing process. The larger the particle size, the larger the cross-sectional area of ​​the abrasive particles pressed into the glass surface, the stronger the mechanical effect, and the higher the removal efficiency. By introducing small-particle cerium oxide B polishing powder, the total number of abrasive particles per unit volume (high packing density) and specific surface area are increased, and small-particle polishing powder is more easily adsorbed on the concave parts of the glass surface or around large-particle polishing powder, preventing large-particle cerium oxide A from excessively removing the concave parts of the substrate surface, which is beneficial to the flattening of the substrate during the polishing process.

[0012] The large-particle cerium oxide A and the small-particle cerium oxide B cooperate with each other to improve the polishing rate and polishing surface quality of the polishing powder. If the particle size of cerium oxide A is too large or the content is too high, it is easy to cause scratches. If the particle size of cerium oxide A is too small or the content is too low, the polishing efficiency is slow. Therefore, through the reasonable combination of particle size and ratio of cerium oxide A and cerium oxide B, the polishing efficiency and polishing surface quality can be better taken into account.

[0013] In some embodiments, the particle size D50 of the cerium oxide A is 0.9-1.2 μm, specifically 0.9 μm, 1 μm, 1.1 μm, 1.2 μm or any value therebetween.

[0014] In some embodiments, the particle size D50 of the cerium oxide B is 0.4-0.6 μm, specifically 0.4 μm, 0.45 μm, 0.5 μm, 0.55 μm, 0.6 μm or any value therebetween.

[0015] In some embodiments, the particle size D50 of the cerium oxide B is 0.4-0.5 μm.

[0016] The surface quality of the substrate can be better improved by properly matching the particle size of cerium oxide.

[0017] In some embodiments, the mass percentage of the cerium oxide B is 15% to 35%, specifically 15%, 20%, 25%, 30%, 35% or any value therebetween.

[0018] In some embodiments, the mass percentage of the cerium oxide B is 20% to 25%.

[0019] In some embodiments, the cerium oxide B is further doped with fluorine, wherein the fluorine content is 1% to 10% of the mass of the cerium oxide B, specifically 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or any value therebetween. Appropriate doping with fluorine can improve the polishing performance of the polishing powder and obtain faster removal efficiency.

[0020] In some embodiments, the cerium oxide B is doped with fluorine at a mass concentration of 2% to 6%.

[0021] A second aspect of the present invention provides a polishing liquid, wherein the raw materials for preparing the polishing liquid include a dispersed phase and the above-mentioned polishing powder.

[0022] The polishing liquid contains cerium oxide A and cerium oxide B with different particle sizes as abrasives, which fully utilizes the advantages of large-particle cerium oxide A and small-particle large-particle cerium oxide B, thereby achieving a common improvement in polishing rate and polishing surface quality.

[0023] In some embodiments, the mass concentration of the polishing powder in the polishing liquid is 3% to 15%, for example, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15% or any value therebetween, which can be adjusted according to the process requirements and is not restrictive.

[0024] In some embodiments, the dispersed phase is water.

[0025] In some embodiments, the raw materials for preparing the polishing liquid also include a dispersant for improving the dispersibility of the powder and reducing aggregation and sedimentation.

[0026] In some embodiments, the dispersant is selected from at least one of sodium hexametaphosphate, polyethylene glycol, citrate, and sodium polycarboxylate.

[0027] In some embodiments, the mass concentration of the dispersant is 0.2% to 2%, specifically 0.2%, 0.5%, 1%, 1.5%, 2% or any value therebetween. Further, the mass concentration of the dispersant is 0.5% to 1%.

[0028] In some embodiments, the pH of the polishing liquid is 9-12. Specifically, the pH can be adjusted to the target range by adding a common pH adjuster in the art, such as sodium hydroxide, potassium hydroxide, etc. Under weak alkaline conditions, it is more conducive to improving the polishing efficiency.

[0029] A third aspect of the present invention provides a method for preparing the polishing liquid, comprising:

[0030] Providing a cerium-containing precursor and performing a first calcination to obtain the cerium oxide A;

[0031] The cerium salt and the precipitant are reacted in the presence of a solvent to obtain a precipitate, and the precipitate is subjected to a second calcination to obtain the cerium oxide B;

[0032] The raw materials including the cerium oxide A, cerium oxide B and dispersed phase are mixed to obtain a polishing liquid.

[0033] The thermal decomposition method is highly efficient, and the co-precipitation method is conducive to particle refinement. The combination of the two processes can improve production efficiency and meet the requirements of industrial production.

[0034] In some embodiments, the cerium-containing precursor is Ce(OH) 3 Or Ce 2 (CO 3 ) 3 It is a conventional commercial raw material, which can usually be extracted from rare earth ores. It has lower raw material cost than the co-precipitation method. After calcination, the particle size is larger and the particle size distribution is wider. It can be refined by processes such as ball milling.

[0035] In some embodiments, the method for preparing the cerium oxide A further comprises: performing ball milling after the first calcination to obtain the cerium oxide A.

[0036] The present invention does not impose any restrictive provisions on the ball milling process parameters. Specifically, the target particle size can be obtained by adjusting the ball milling bead gradation, ball-to-material ratio, rotation speed, ball milling time, etc.

[0037] In some embodiments, the temperature of the first calcination is 800°C-950°C, and the time of the first calcination is 4-12h. In the above calcination temperature and time range, it is beneficial to obtain high-quality cerium oxide with suitable particle size, wherein the influence of calcination temperature is relatively more significant. Specifically, the temperature of the first calcination is 800°C, 850°C, 900°C, 950°C or any value therebetween. The time of the first calcination is 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h or any value therebetween.

[0038] In some embodiments, when the cerium oxide B is doped with fluorine, the method for preparing the precipitate comprises: reacting a cerium salt, a precipitant and hydrofluoric acid in the presence of a solvent to obtain. Specifically, the amount of hydrofluoric acid added is determined according to the fluorine doping amount.

[0039] In some embodiments, the reaction temperature is 70-90°C, and the reaction time is 1-3 hours. Specifically, the reaction temperature is 70°C, 75°C, 80°C, 85°C, 90°C, or any value therebetween. The reaction time is 1 hour, 2 hours, 3 hours, or any value therebetween.

[0040] In some embodiments, the cerium salt includes at least one of cerium nitrate, cerium chloride, and cerium sulfate.

[0041] In some embodiments, the precipitant includes at least one of ammonium bicarbonate, aqueous ammonia, sodium carbonate, and sodium hydroxide.

[0042] In some embodiments, the temperature of the second calcination is 800°C-950°C, and the time of the second calcination is 4-12 hours. Specifically, the temperature of the second calcination is 800°C, 850°C, 900°C, 950°C, or any value therebetween. The time of the second calcination is 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, or any value therebetween.

[0043] In some embodiments, before the second calcination, the precipitate is further washed and dried.

[0044] In some embodiments, the solvent is water.

[0045] In some embodiments, when the raw materials for preparing the polishing liquid further include a dispersant, the dispersant is mixed with the cerium oxide A, the cerium oxide B, and the dispersed phase.

[0046] In some embodiments, the step of adjusting the pH of the polishing liquid is further included, for example, using the pH adjusting agent listed above to adjust the pH to 9-12.

[0047] A third aspect of the present invention relates to the use of the above-mentioned polishing powder or polishing liquid in polishing a quartz substrate, or in preparing a photomask or an integrated circuit.

[0048] Since polishing powder or polishing liquid can take into account both polishing efficiency and polishing surface quality, a quartz substrate with higher surface quality can be obtained, which better meets the production requirements of integrated circuits.

[0049] When referring to numerical ranges herein, all numerical ranges include the endpoints and any subset ranges within the range.

[0050] Other features and advantages of the present invention will be set forth in the description which follows, and in part will be apparent from the description, or may be learned by practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0051] Figure 1 This is the roughness test result of Example 1.

[0052] Figure 2 This is the roughness test result of Example 2.

[0053] Figure 3 This is the roughness test result of Example 3.

[0054] Figure 4 This is the roughness test result of Comparative Example 1.

[0055] Figure 5 This is the roughness test result of Example 2.

[0056] Figure 6 This is the roughness test result of Example 3. DETAILED DESCRIPTION

[0057] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention.

[0058] In the following examples, the raw materials involved are all commercially available conventional products unless otherwise specified.

[0059] Example 1

[0060] A polishing liquid is prepared, comprising the steps of:

[0061] S1, Ce 2 (CO 3 ) 3 Calcinated at 900°C for 8 h and ball milled to obtain cerium oxide A with a particle size D50 of 1.1 μm;

[0062] Cerium nitrate is used as the cerium salt, ammonium bicarbonate is used as the precipitant, and deionized water is used as the dispersed phase. At the same time, hydrofluoric acid is added to the solution, and the reaction is carried out at 80°C for 2 hours. The mixture is filtered, washed, and dried to obtain a fluorine-doped cerium carbonate precipitate. The precipitate is calcined at 900°C for 8 hours to obtain cerium oxide B (fluorine-doped cerium oxide, the fluorine doping amount is 5wt%, and cerium nitrate, ammonium bicarbonate, and hydrofluoric acid are added in chemical equivalents) with a particle size D50 of 0.45μm.

[0063] S2. Disperse cerium oxide A, cerium oxide B and a dispersant in water, adjust the pH to 9-12 with sodium hydroxide to obtain a polishing liquid, wherein cerium oxide B accounts for 20% of the total mass of cerium oxide A and cerium oxide B; the mass concentration of cerium oxide A and cerium oxide B is 8%; and the dispersant is sodium polycarboxylate with a mass concentration of 0.5%.

[0064] The prepared polishing liquid was used to double-sided polish the synthetic quartz glass substrate on a double-sided polishing machine, and the polishing pad used was a polyurethane polishing pad. After polishing, the quartz glass substrate was ultrasonically treated in pure water, alkaline, and acidic solutions, respectively, and then dried after cleaning. The flatness of the substrate was detected by a laser interferometer, and the PV value was 0.2μm. The surface roughness was measured under a white light interferometer and was 0.4nm (such as Figure 1 shown).

[0065] Example 2

[0066] A polishing liquid is prepared, comprising the steps of:

[0067] S1, Ce 2 (CO 3 ) 3 Calcinated at 900°C for 8 h and ball milled to obtain cerium oxide A with a particle size D50 of 1.1 μm;

[0068] Cerium nitrate is used as the cerium salt, ammonium bicarbonate is used as the precipitant, and deionized water is used as the dispersed phase. At the same time, hydrofluoric acid is added to the solution, and the reaction is carried out at 80°C for 2 hours. The mixture is filtered, washed, and dried to obtain a fluorine-doped cerium carbonate precipitate. The precipitate is calcined at 900°C for 8 hours to obtain cerium oxide B (fluorine-doped cerium oxide, the fluorine doping amount is 5wt%, and cerium nitrate, ammonium bicarbonate, and hydrofluoric acid are added in chemical equivalents) with a particle size D50 of 0.55μm.

[0069] S2. Disperse cerium oxide A, cerium oxide B and a dispersant in water, adjust the pH to 9-12 with sodium hydroxide to obtain a polishing liquid, wherein cerium oxide B accounts for 15% of the total mass of cerium oxide A and cerium oxide B; the mass concentration of cerium oxide A and cerium oxide B is 8%; and the dispersant is sodium hexametaphosphate with a mass concentration of 0.6%.

[0070] The prepared polishing liquid was used to double-sided polish the synthetic quartz glass substrate on a double-sided polishing machine, and the polishing pad used was a polyurethane polishing pad. After polishing, the quartz glass substrate was ultrasonically treated in pure water, alkaline, and acidic solutions, respectively, and then dried after cleaning. The flatness of the substrate was detected by laser interferometer, and the PV value was 0.5μm. The surface roughness was measured under white light interferometer and was 0.5nm (such as Figure 2 shown).

[0071] Example 3

[0072] A polishing liquid is prepared, comprising the steps of:

[0073] S1, Ce 2 (CO 3 ) 3 Calcinated at 900°C for 8 h and ball milled to obtain cerium oxide A with a particle size D50 of 1.1 μm;

[0074] Cerium nitrate is used as the cerium salt, ammonium bicarbonate is used as the precipitant, and deionized water is used as the dispersed phase. At the same time, hydrofluoric acid is added to the solution, and the reaction is carried out at 80°C for 2 hours. The mixture is filtered, washed, and dried to obtain a fluorine-doped cerium carbonate precipitate. The precipitate is calcined at 900°C for 8 hours to obtain cerium oxide B (fluorine-doped cerium oxide, the fluorine doping amount is 5wt%, and cerium nitrate, ammonium bicarbonate, and hydrofluoric acid are added in chemical equivalents) with a particle size D50 of 0.55μm.

[0075] S2. Disperse cerium oxide A, cerium oxide B and a dispersant in water, adjust the pH to 9-12 with sodium hydroxide to obtain a polishing liquid, wherein cerium oxide B accounts for 35% of the total mass of cerium oxide A and cerium oxide B; the mass concentration of cerium oxide A and cerium oxide B is 8%; and the dispersant is sodium hexametaphosphate with a mass concentration of 0.5%.

[0076] The prepared polishing liquid was used to double-sided polish the synthetic quartz glass substrate on a double-sided polishing machine, and the polishing pad used was a polyurethane polishing pad. After polishing, the quartz glass substrate was ultrasonically treated in pure water, alkaline, and acidic solutions, respectively, and then dried after cleaning. The flatness of the substrate was detected by laser interferometer, and the PV value was 0.4μm. The surface roughness was measured under white light interferometer and was 0.5nm (such as Figure 3 shown).

[0077] Comparative Example 1

[0078] A polishing liquid is prepared, comprising the steps of:

[0079] S1, Ce 2 (CO 3 ) 3 The cerium oxide A with a particle size D50 of 1.1 μm was obtained by calcining at 900°C for 8 h and ball milling.

[0080] S2. Dispersing cerium oxide A and a dispersant in water, adjusting the pH to 9-12 with sodium hydroxide, and obtaining a polishing liquid, wherein the mass concentration of cerium oxide A is 8%; and the dispersant is sodium polycarboxylate, and the mass concentration is 0.5%.

[0081] The prepared polishing liquid was used to double-sided polish the synthetic quartz glass substrate on a double-sided polishing machine, and the polishing pad used was a polyurethane polishing pad. After polishing, the quartz glass substrate was ultrasonically treated in pure water, alkaline, and acidic solutions, and then dried after cleaning. The flatness of the substrate was detected by laser interferometer, and the PV value was 0.7μm. The surface roughness was measured by white light interferometer and was 0.7nm (such as Figure 4 shown).

[0082] Comparative Example 2

[0083] A polishing liquid is prepared, comprising the steps of:

[0084] S1, Ce 2 (CO 3 ) 3 Calcinated at 900°C for 8 h and ball milled to obtain cerium oxide A with a particle size D50 of 1.1 μm;

[0085] Cerium nitrate is used as the cerium salt, ammonium bicarbonate is used as the precipitant, and deionized water is used as the dispersed phase. At the same time, hydrofluoric acid is added to the solution, and the reaction is carried out at 80°C for 2 hours. The mixture is filtered, washed, and dried to obtain a fluorine-doped cerium carbonate precipitate. The precipitate is calcined at 1000°C for 12 hours to obtain cerium oxide B (fluorine-doped cerium oxide, the fluorine doping amount is 5wt%, cerium nitrate, ammonium bicarbonate, and hydrofluoric acid are added in chemical equivalents) with a particle size D50 of 0.9μm.

[0086] S2. Disperse cerium oxide A, cerium oxide B and a dispersant in water, adjust the pH to 9-12 with sodium hydroxide to obtain a polishing liquid, wherein cerium oxide B accounts for 5% of the total mass of cerium oxide A and cerium oxide B; the mass concentration of cerium oxide A and cerium oxide B is 8%; and the dispersant is sodium hexametaphosphate with a mass concentration of 0.3%.

[0087] The prepared polishing liquid was used to double-sided polish the synthetic quartz glass substrate on a double-sided polishing machine, and the polishing pad used was a polyurethane polishing pad. After polishing, the quartz glass substrate was ultrasonically treated in pure water, alkaline, and acidic solutions, respectively, and then dried after cleaning. The flatness of the substrate was detected by laser interferometer, and the PV value was 0.7μm. The surface roughness was measured by white light interferometer and was 0.7nm (such as Figure 5 shown).

[0088] Comparative Example 3

[0089] A polishing liquid is prepared, comprising the steps of:

[0090] S1, Ce 2 (CO 3 ) 3 Calcinated at 900°C for 8 h and ball milled to obtain cerium oxide A with a particle size D50 of 1.1 μm;

[0091] Cerium nitrate is used as the cerium salt, ammonium bicarbonate is used as the precipitant, and deionized water is used as the dispersed phase. At the same time, hydrofluoric acid is added to the solution, and the reaction is carried out at 80°C for 2 hours. The mixture is filtered, washed, and dried to obtain a fluorine-doped cerium carbonate precipitate. The precipitate is calcined at 1000°C for 12 hours to obtain cerium oxide B (fluorine-doped cerium oxide, the fluorine doping amount is 5wt%, cerium nitrate, ammonium bicarbonate, and hydrofluoric acid are added in chemical equivalents) with a particle size D50 of 0.9μm.

[0092] S2. Disperse cerium oxide A, cerium oxide B and a dispersant in water, adjust the pH to 9-12 with sodium hydroxide to obtain a polishing liquid, wherein cerium oxide B accounts for 50% of the total mass of cerium oxide A and cerium oxide B; the mass concentration of cerium oxide A and cerium oxide B is 8%; and the dispersant is sodium hexametaphosphate with a mass concentration of 0.4%.

[0093] The prepared polishing liquid was used to double-sided polish the synthetic quartz glass substrate on a double-sided polishing machine, and the polishing pad used was a polyurethane polishing pad. After polishing, the quartz glass substrate was ultrasonically treated in pure water, alkaline, and acidic solutions, respectively, and then dried after cleaning. The flatness of the substrate was detected by laser interferometer, and the PV value was 0.6μm. The surface roughness was measured by white light interferometer and was 0.6nm (such as Figure 6 shown).

[0094] In summary, the polishing liquid prepared by this embodiment has lower polishing PV value and roughness, has better surface quality, and can better meet the production requirements of integrated circuits. In addition, the presence of large-particle cerium oxide A can also ensure polishing efficiency and meet the needs of efficient production.

[0095] The embodiments of the present invention are described in detail above, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge scope of ordinary technicians in the relevant technical field without departing from the purpose of the present invention.

Claims

1. A polishing powder, characterized in that: include: Cerium oxide A with a particle size D50 of 0.8 to 1.5 μm and cerium oxide B with a particle size D50 of 0.1 to 0.6 μm, wherein the mass percentage of the cerium oxide B is 10% to 40%.

2. The polishing powder according to claim 1, characterized in that The cerium oxide B is also doped with fluorine, wherein the fluorine content is 1% to 10% of the mass of the cerium oxide B.

3. The polishing powder according to claim 1, characterized in that The particle size D50 of the cerium oxide A is 0.9-1.2 μm; and / or the particle size D50 of the cerium oxide B is 0.4-0.6 μm; and / or the mass percentage of the cerium oxide B is 15%-35%.

4. A polishing liquid, characterized in that: The preparation raw materials include a dispersed phase and the polishing powder as described in any one of claims 1 to 3.

5. The polishing liquid according to claim 4, characterized in that: The mass concentration of the polishing powder is 3% to 15%; and / or the dispersed phase is water; and / or the pH of the polishing liquid is 9-12.

6. The polishing liquid according to claim 4, characterized in that The raw materials for preparing the polishing liquid also include a dispersant.

7. The polishing liquid according to claim 6, characterized in that The dispersant is selected from at least one of sodium hexametaphosphate, polyethylene glycol, citrate, and sodium polycarboxylate; and / or the mass concentration of the dispersant is 0.2% to 2%.

8. The method for preparing the polishing liquid according to any one of claims 4 to 7, characterized in that: include: Providing a cerium-containing precursor and performing a first calcination to obtain the cerium oxide A; The cerium salt and the precipitant are reacted in the presence of a solvent to obtain a precipitate, and the precipitate is subjected to a second calcination to obtain the cerium oxide B; The raw materials including the cerium oxide A, cerium oxide B and dispersed phase are mixed to obtain a polishing liquid.

9. The preparation method according to claim 8, characterized in that: The preparation method of cerium oxide A further comprises: ball milling after the first calcination; and / or, the temperature of the first calcination is 800° C.-950° C., and the time of the first calcination is 4-12 hours; and / or, the cerium-containing precursor is Ce(OH)3 or Ce2(CO3)3; And / or, when the cerium oxide B is doped with fluorine, the method for preparing the precipitate comprises: reacting a cerium salt, a precipitant and hydrofluoric acid in the presence of a solvent to obtain; and / or, the reaction temperature is 70-90°C, and the reaction time is 1-3h; and / or, the cerium salt comprises at least one of cerium nitrate, cerium chloride and cerium sulfate; and / or, the precipitant comprises at least one of ammonium bicarbonate, ammonia water, sodium carbonate and sodium hydroxide; and / or, the second calcination temperature is 800°C-950°C, and the second calcination time is 4-12h; and / or, the solvent is water; And / or, when the raw materials for preparing the polishing liquid also include a dispersant, the dispersant is mixed with the cerium oxide A, cerium oxide B, and the dispersed phase; and / or, the method further includes a step of adjusting the pH of the polishing liquid.

10. Use of the polishing powder according to any one of claims 1 to 3 or the polishing liquid according to any one of claims 4 to 7 in polishing a quartz substrate, or in preparing a photomask or an integrated circuit.